2019
DOI: 10.1001/jamanetworkopen.2018.7665
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment After a Severe Hospital-Acquired Infection Associated With Carbapenemase-Producing Pseudomonas aeruginosa

Abstract: Importance Resistance of gram-negative bacilli to carbapenems is rapidly emerging worldwide. In 2016, the World Health Organization defined the hospital-built environment as a core component of infection prevention and control programs. The hospital-built environment has recently been reported as a source for outbreaks and sporadic transmission events of carbapenemase-producing gram-negative bacilli from the environment to patients. Objective To assess risk after the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 20 publications
3
31
0
2
Order By: Relevance
“…P. aeruginosa can reside in the sink drains in the patient room for long periods. The spreading and distribution of MDR P. aeruginosa in the shower and sink drains, and sewage system of the ward is quite complex as several studies have shown [11, 34]. We found direct and indirect evidence for both modes of transmission (patient-to-patient and room-to-patient).…”
Section: Discussionsupporting
confidence: 51%
“…P. aeruginosa can reside in the sink drains in the patient room for long periods. The spreading and distribution of MDR P. aeruginosa in the shower and sink drains, and sewage system of the ward is quite complex as several studies have shown [11, 34]. We found direct and indirect evidence for both modes of transmission (patient-to-patient and room-to-patient).…”
Section: Discussionsupporting
confidence: 51%
“…In a CR Sphingomonas koreensis outbreak, sink aerators, faucets, mixing valves, pipes and other plumbing fixtures were also found to be contaminated [24]. Shower drains have also been implicated with CRPA outbreak [25]. In a study by Stjärne et al, investigation of a CRPA outbreak revealed contamination of sinks with isolates closely related to CRPA from patients [23].…”
Section: Outbreak Reportsmentioning
confidence: 99%
“…Retrograde contamination from common sewage pipes can also occur in showers [25]. The use of showers may result in airborne or droplet transmission from shower drains to patients.…”
Section: Outbreak Reportsmentioning
confidence: 99%
“…Maar toch blijven ook voor Nederland veel riskante situaties (Hopman et al, 2019). Daarbij is AMR ook een globale problematiek en is het dus ook belangrijk om beleidsmatig op mogelijke epidemieën en uitbraken te anticiperen.…”
Section: 4unclassified